Advances in parasitology. Volume 53 - Baker, John R. (John Robin); Muller, Ralph, 1933-; Rollinson, D.; ScienceDirect eBooks (Amsterdam : Academic Press, 2003)
First published in 1963, Advances in Parasitology contains comprehensive and up-to-date reviews in all areas of interest in contemporary parasitology. Now edited by J.R. Baker, R. Muller, and D. Rollinson, and supported by an international editorial board, Advances in Parasitology includes medical studies on parasites of major influence, such as typanosomiasis and scabies, and reviews of more traditional areas, such as zoology, taxonomy, and life history. Eclectic volumes are supplemented by thematic volumes on such topics as Remote Sensing and Geographical Information Systems in Epidemiology.
Interactions between Tsetse and Trypanosomes with Implications for the Control of Trypanosomiasis; Enzymes Involved in the Biogenesis of the Nematode Cuticle; Diagnosis of Human Filariases (Except Onchocerciasis); INDEX; CONTENTS OF VOLUMES IN THIS SERIES.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Parasitology; Medical parasitology; MEDICAL -- Parasitology; Medical parasitology; Parasitology; Electronic books